TOURISM EXPORT DEVELOPMENT IN UZBEKISTAN: THE ROLE OF INSTITUTIONS AND REGIONAL INTEGRATION - Akmal Bakhromov (Modern American Journals, 2025)
This research article investigates the role of institutional factors and regional integration in the development of tourism services exports in Uzbekistan. Drawing on institutional economics and theories of comparative advantage, the study explores how formal institutions (e.g., regulatory quality, policy implementation) and informal institutions (e.g., trust networks, cultural affinity) shape the trajectory of tourism exports. A comparative analysis with Kazakhstan and Turkey has been conducted using a qualitative-dominant mixed-methods approach that includes institutional benchmarking, policy review, and statistical data analysis.
Keywords: Tourism services export, institutional factors, regional integration, Uzbekistan, Kazakhstan, Turkey, informal institutions, comparative analysis.